Effect of histone demethylase KDM5B on long-term cognitive impairment in neonatal rats induced by sevoflurane - Wang, Yanhong; Chen, Yun; Zhang, Mengxiao; Yuan, Chengdong; Zhang, Yu; Liu, Xingjian; Zhang, Yi; Liang, Xiaoli (Frontiers in Molecular Neuroscience, 2024)
IntroductionWhether repeated inhalation of sevoflurane during the neonatal period causes long-term learning and memory impairments in humans is unclear. Some recent investigations have indicated that general anesthesia drugs affect histone methylation modification and may further affect learning and memory ability. This study aimed to explore the role and mechanism of histone methylation in long-term cognitive dysfunction caused by repeated inhalation of sevoflurane during the neonatal period.MethodsNeonatal SD rats were assigned into three groups. Sevoflurane group and sevoflurane +AS8351 group were exposed to 2% sevoflurane for 4 h on postnatal day 7 (P7), day 14 (P7) and day 21 (P21), and the control group was inhaled the air oxygen mixture at the same time. From postnatal day 22 to 36, rats in the +AS8351 group were treated with AS8351 while those in the Sevoflurane group and control group were treated with normal saline. Half of the rats were carried out Y-maze, Morris water maze (MWM), western blot and transmission electron microscope at P37, and the remaining rats were fed to P97 for the same experiment.ResultsNeonatal sevoflurane exposure affected histone demethylase expression in hippocampus, changed histone methylation levels, Down-regulated synapse-associated protein expression, impaired synaptic plasticity and long-term cognitive dysfunction and KDM5B inhibitors partially restored the negative reaction caused by sevoflurane exposure.DiscussionIn conclusion, KDM5B inhibitor can save the long-term learning and memory impairment caused by sevoflurane exposure in neonatal period by inhibiting KDM5B activity.